Migrant Farmworkers and Their Children Philip Martin. - Martin, Philip (ERIC digest., 1994)
This digest reviews the population characteristics of migrant and seasonal farmworkers and their children. Since the 1960s, federal programs for migrant workers and their families have multiplied. However, these programs have differing definitions for "migrant and seasonal farmworker," and no current data system provides a reliable count or profile of migrant children. In 1989 the U.S. Department of Labor initiated the National Agricultural Worker Survey (NAWS) to address fears that immigration reform would result in farm labor shortages. Considered by some researchers to be the best data currently available, NAWS suggests that, in 1989-91, there were about 840,000 migrant farmworkers who had 409,000 children traveling with them. Of these children, 36,000 also did farmwork. An additional 169,000 youth were farmworkers traveling without their parents. Migrant farmworkers were primarily Hispanics (94%), born in Mexico (80%), married with children (52%), in the United States without their families (59%), and mostly men (82%). Migrant farmworkers are the largest needy labor force in the United States. Their numbers are unlikely to diminish as labor-intensive crops make up over a third of total U.S. crop sales. Economic dislocation in rural Mexico is expected to accelerate Mexican immigration in the 1990s, and many new immigrants will speak Indian languages rather than Spanish. Programs that serve migrant farmworkers and their children will need flexibility to deal with this changing population. (SV)